2022
DOI: 10.3390/jcm11123418
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Aortic Prosthetic Valve Endocarditis in the Transcatheter Era

Abstract: Objectives: As surgical experience with infective endocarditis following transcatheter aortic valve replacement is scarce, this study compared the perioperative and short-term outcomes of patients suffering from endocarditis following surgical aortic valve replacement and transcatheter aortic valve replacement. Methods: Between January 2013 and December 2020, 468 consecutive patients were admitted to our center for surgery for IE. Among them, 98 were operated on for endocarditis following surgical aortic valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Although the current literature fails to demonstrate significantly better outcomes of surgery compared to conservative therapy in patients with TAVI PVE presenting with a high-risk profile [ 33 , 34 ], the most current data from the mid- and low-risk cohorts suggest that the outcomes after surgery tend to mimic those of patients presenting with PVE following SAVR [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the current literature fails to demonstrate significantly better outcomes of surgery compared to conservative therapy in patients with TAVI PVE presenting with a high-risk profile [ 33 , 34 ], the most current data from the mid- and low-risk cohorts suggest that the outcomes after surgery tend to mimic those of patients presenting with PVE following SAVR [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Explantation and replacement of the aortic valve under the blanket of intravenous antibiotics are currently recommended [ 7 ]. We suggest early initiation of antibiotics in the elderly with a similar profile especially on receiving a preliminary report of positive blood culture.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a multicenter registry in Germany showed that the incidence of root surgery was 14.5% during operations for THV IE [34], which is not more common than in native aortic valve IE (16.8%) [35]. The incidence of root abscess is also not different in IE after TAVR and conventional surgical valve replacement [36]. The decision to operate should be weighed against the surgical risk profile of the patient and made within the confines of an endocarditis team [37].…”
Section: Infective Endocarditismentioning
confidence: 99%
“…The mortality rates for TAVR IE are high, ranging from 16 to 36% for in-hospital mortality and 41-59% at 1-year [20,[25][26][27]. Notwithstanding, the results of operative management of TAVR IE are not significantly different than those of surgical valve IE [36]. In the report of the ESC-EORP EURO-ENDO (European Infective Endocarditis Registry), the strongest predictor of mortality in IE was not performing surgery when indications were present [38].…”
Section: Infective Endocarditismentioning
confidence: 99%